The Role of Tax Knowledge and Awareness in Improving Tax Compliance: A Systematic Review - Agung Nurmansyah; Norman Duma Sitinjak; Dahlan Susilo (CV. Sakura Digital Nusantara, 2026)
Purpose - This article examines the role of tax knowledge and tax awareness in improving tax compliance. The topic is important because compliance depends not only on taxpayers’ understanding of tax rules, but also on motivational and administrative factors. Design/methodology/approach - This study used a Systematic Literature Review guided by the PRISMA framework. Articles were collected from the Directory of Open Access Journals and limited to peer-reviewed studies published between 2022 and 2026. Selected studies were analyzed using qualitative descriptive synthesis. Findings/Results - The review shows that tax knowledge generally improves tax compliance by strengthening understanding of tax obligations and procedures, while tax awareness is a more consistent driver of compliant behavior. The findings also indicate that tax education, socialization, trust, fairness, service quality, and user-friendly digital systems reinforce compliance outcomes. Originality/Value - This study presents tax compliance as a behavioral and institutional outcome shaped by cognitive, attitudinal, and administrative factors. The main implication is that efforts to strengthen voluntary compliance should combine taxpayer education, awareness building, fair administration, and accessible digital services.